IMPLEMENTASI NILAI-NILAI AGAMA SEBAGAI PENYELESAIAN KONFLIK BULLYING VERBAL PADA SISWA KELAS VII DI SMP NEGERI 4 SAMBAS - Agustian; Astaman; Mauizatul Hasanah (JIP: Jurnal Ilmu Pendidikan, 2026)
This study aims to: (1) identify the factors underlying verbal bullying among seventh-grade students at SMP Negeri 4 Sambas; (2) describe the implementation of religious values as a strategy to resolve verbal bullying conflicts; and (3) analyze the impact of implementing religious values in addressing verbal bullying. This research employed a qualitative approach with a phenomenological design. Primary data were obtained from six informants, including an Islamic Education teacher, the school principal, a guidance and counseling teacher, and three seventh-grade students (two from class VII C and one from VII D). Secondary data included documents, photographs, and relevant records. Data were collected through interviews, observations, and documentation. The data analysis techniques involved data reduction, data display, and conclusion drawing, while data validity was ensured through source triangulation and member checking. The findings reveal that the factors contributing to verbal bullying include: (a) differences in religion and social class, (b) uncontrolled seniority, (c) family disharmony, (d) less supportive school environment, (e) negative behavior modeled by teachers, and (f) peer group characteristics. The implementation of religious values is carried out through: (a) integration of religious values across subjects, (b) habituation of religious activities, (c) active involvement of guidance and counseling teachers, (d) tiered intervention strategies, and (e) anti-bullying campaigns. The impacts of this implementation include: (a) behavioral changes in students, (b) increased tolerance, (c) development of empathy, (d) enhanced spiritual awareness regarding sinful behavior, and (e) the creation of a more conducive school environment.